CAUSE AND EFFECT RELATION BETWEEN THE CURRENT MIGRATIONS AND TERRORISM IN WESTERN EUROPE - Cvetkovic, Nedeljko; Vujović, Danilo (NBP. Nauka, bezbednost, policija, 2019)
The key subject analyzed within this article - the existence, and character, of the cause and effect connection in regard to the current migrant crisis and the rise of terrorist activity in Western Europe – required first a look back at the terms terrorism and migration, their respective characterisitics, as well as the geopolitical factors affecting them; secondly, it required an analysis of their mutual interaction; and finally, a comparison of the points of view taken by all the parties involved when approaching this problem, as well as determining certain potential solutions to the myriad of problems caused by the migrant crisis. This subject, we feel, is relevant due to the important role terrorism has in causing the migration of muslim population from Africa and the Middle East toward the European Union, as well as the potential effect of the said migration on the spreading of terrorism within Europe itself. Whilst researching the literature needed to write this article, the authors used the method of content analysis. Existence of the direct link between terrorism -as one of the causes of migrations, and migrations - as a condition helping the expansion of terrorism into Europe, presents itself as a result of the conducted research.